Family violence reported to the police station specialized in family affairs in the town of funza, cundinamarca (2001)
Family violence in its multiple forms, i.e, verbal aggression, psychological, economical, sexual and physical abuse, has become a structural phenomenon of society which yields countless victims. The loss of years of life, the transient or permanent leaves from work, and perpetuation of its vicious cir cle make of it a challenge for public health in general and for society as a whole. The main violent events generated within the family and the principal characteristics of its actors were assessed by means of a retrospective study in a population of 374 registered cases reported to the police station specialized in family affairs of the town of Funza, Cundinamarca. Young adults are the group of population which most frequently suffer these aggressions and within it women are most often offended. The person responsible for this violence is usually someone known within the family group and in the majority of cases the victims themselves maid the claim. On the other hand, verbal and economic violence are the most frequent forms, followed by psychological and physical violence.